Structural and electrical characteristics of rhombohedral lead zirconate titanate single crystals - Perez, J. A.
Two PbZrxTi1-xO3 (PZT) single crystals, from a batch prepared by the flux method, were analysed to assess their chemical composition. The two single crystals were found by electron microprobe analysis to have the chemical compositions PbZr0.60Ti0.40O3 and PbZr0.65 Ti0.35O3. X-ray diffraction at -93 degrees C revealed that both crystals have the R3m space group, which means that the R3m <-> R3c phase transition is not observed in this composition range for temperatures above -93 degrees C. The dielectric permittivity was measured along the [001] direction at several frequencies from 1 kHz to 1 MHz, at varying temperatures up to 460 degrees C, and the parameters of the Curie-Weiss law were determined. The parameters of a thermodynamic model for the rhombohedral phase were determined by fitting the experimental data with the theoretical model. The polarization was calculated as function of the temperature for both crystals and the results were used to observe the order of the phase transition. The polarization increases when the concentration of PZT approaches the morphotropic region from the rhombohedral side. This fact, already observed in ceramic samples, is for the first time reported in single crystals which contributes for the clarification of the maximum of electrical properties in the morphotropic region.